Revitalization and Socialization of Daeng Dance in Purbalingga, Indonesia - Anggraeni, Dinar (Department of Drama, Dance, and Musik (Sendratasik), Semarang State University, 2015)
The purpose of the study is to know and depict the revitalization and socialization of Daeng dance in purbalingga, Indonesia. This study used a qualitative method. The relevant techniques of data collection to the method are observation, interview, and documentation. The data obtained are analyzedusing three ways; they are data reduction, data display, conclusion and verification. The results showed that revitalizing Daeng dance occurred in its earliest performances, by means of innovating the foregoing Daeng dance without leaving its characteristics. The revitalization was done toward the danceâs motion, accompaniment, makeup, wardrobe, stage, sounds, lighting, and floor patterns, as well as there is a change in its function; as the media of spreading Islam in the past to nowadays just being an entertainment. After the process of revitalization, Daeng dance is then socialized through two ways of deployment; they are formal and informal processes. This danceâs socialization in this study occurs through direct performance and mass media.Â